The Struggle for Persia (RLE Iran A) - Stuart, Donald (Routledge Library Editions: Iran., 2012)
This volume is an account of the journey the author made between Eastern Russia (via Tabriz) to Teheran at the turn of the twentieth century. This is not just a travelogue, however, but a lament for the loss of British "prestige" and power in the region to Russia.